The Extraordinary Equatorial Atlantic Warming in Late 2019 - Richter, Ingo; Tokinaga, Hiroki; Okumura, Yuko M. (Geophysical research letters, 2022)
Sea‐surface temperatures (SSTs) in the eastern equatorial Atlantic are subject to variability on interannual timescales but during the last 20 years, this variability has shown comparatively little activity. In late 2019, however, the warmest event in the satellite observation period developed. Analysis suggests that zonal wind stress anomalies in the western equatorial Atlantic contributed to the development of the warm SST anomalies. Furthermore, wind stress curl anomalies north of the equator generated downwelling Rossby waves that propagated to the western boundary and were reflected into downwelling Kelvin waves that helped to precondition the event. Neither the contemporaneous positive Indian Ocean Dipole nor the El Niño Modoki appears to have contributed substantially to the Atlantic warming, though some uncertainty remains. Based on large‐scale multidecadal variability patterns, a return to enhanced variability is not imminent but careful monitoring will be important. Plain Language Summary Year‐to‐year variability of ocean surface temperatures in the eastern equatorial Atlantic has been relatively weak over the last 20 years. In late 2019, however, an exceptionally strong event developed. This event appears to have been generated by surface wind stress forcing both on and north of the equator. Remote influences from other tropical basins do not seem to have played a large role. Based on large‐scale multidecadal variability patterns in the region, the equatorial Atlantic may return to relatively low variability but continued monitoring will be important. Key Points One of the strongest equatorial Atlantic warm events of the last 40 years developed in late 2019 Wind stress forcing both on and off the equator contributed to the exceptionally strong warming Analysis suggests that remote forcing from other basins was not a major factor in the genesis of the event